Views of primary school supervisors about the use of e-portfolios in educational supervision - Özmen, Fatma; Kömürlü, Fatih (My University, 2011)
E-portfolios have been increasingly utilized in educational supervision in developed countries, as it is done in the various aspects of education. While E-portfolios give the teachers to scrutinize and evaluate their own performance, they offer opportunities to the supervisors to detect and analyze the multifaceted professional development features of teachers in the time, as well. This research is a qualitative study based on the views of primary school supervisors related to the use of e-portfolios in educational supervision. The study group is composed of 62 primary school supervisors who have been working in the cities of Elazi{dotless}?, Malatya, Şanli{dotless}urfa, Hakkari, Gümüşhane, in 2008-2009 instructional year. The supervisors' views which were reflected in the responses given to the open-ended questions, have been obtained by e-mails. Some recommendations have been made concomitant with the findings reached by the analysis of the data, for utilizing e-portfolios in educational supervision.
E?itim denetiminde elektronik ürün dosyasi (e-portfolio) kullanimi hakkinda ilkö?retim denetçilerinin görüşleri1
Keywords: E-portfolios; Educational supervision; Supervision